A closer look into maternal psychological distress and the associated factors: the case of autism and chronic conditions - Cobzeanu, Alexandra; Merlici, Ioan-Alex; Ionescu, Daria Elena; Roca, Iulia Cristina (Frontiers in Psychiatry, 2025)
IntroductionMothers caring for children with autism or chronic illnesses may experience heightened psychological distress due to the ongoing demands associated with caregiving. This study aimed to examine levels of psychological distress among Romanian mothers of children with autism, chronic illness, or typical development, and to explore the role of health-related quality of life and emotion regulation strategies.MethodsA total of 211 Romanian mothers aged 20 to 67 years (M = 38, SD = 8.07) participated in this study. The sample included mothers of children with autism (30.8%), chronic illness (29.4%), and typical development (39.8%). Participants completed self-report questionnaires assessing psychological distress, emotion regulation strategies (cognitive reappraisal and expressive suppression), and health-related quality of life.ResultsHealth-related quality of life was found to be a significant predictor of psychological distress across all participant groups. Additionally, mothers of children with autism reported significantly higher levels of psychological distress compared to mothers of typically developing children.DiscussionThe findings underscore the psychological burden experienced by mothers of children with autism and highlight the importance of targeted support interventions. Addressing psychological distress and its contributing factors may improve the well-being of these caregivers. The results carry important implications for mental health practitioners, researchers, and policymakers aiming to support families managing childhood disability or chronic illness.